The Legal Policy of the Minimum Wage for Workers' Adequate Subsistence - Anis Rukmawati (Journal of Morality and Legal Culture, 2021)
This legal study seeks to determine wage policies through minimum wages in Government Regulation 36 of 2021 concerning Wages in order to provide workers with a decent standard of living and to identify legal certainty guarantees. This is a prescriptive type of normative legal research employing a statute-based methodology. Utilized types of legal materials include primary and secondary legal materials. The technique used to collect legal materials is called "literature collection. In the study technique, the technique used for analyzing legal materials is deduction. The study's findings indicate that the minimum wage outlined in Government Regulation Number 36 of 2021 concerning Wages is insufficient to provide a decent standard of living for workers. First, the formulation has eliminated the indicator for the decent living needs component. Second is the decline in worker or laborer participation in determining the minimum wage. Thirdly, the upper and lower limits now incorporate new variables. Fourth, the formula only offers the option of using the inflation rate or economic growth. Regulation No. 36 of 2021 has failed to provide legal certainty. This is based on 3 benchmarks, the first of which is Firstsharmony between regulations. Second, the content of the rules is unclear, resulting in multiple interpretations. Thirdly, laws from worlusesr are rejected when issuing orders/labor.